2000
DOI: 10.1016/s0261-2194(00)00011-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Flight Control™ and Mesurol® as repellents to reduce horned lark (Eremophila alpestris) damage to lettuce seedlings

Abstract: We conducted enclosure trials near Huron, CA in the San Joaquirl Valley from 12 to 23 January 1999 to de-e the e $ b c y of Flight Controlm(50% anthraquinone) and Mesurol@ (75% methiocarb) in preventing horned lark damage to lettuce seedlings. Flight ControlM (FC) and Mesurolm were evaluated as foliar sprays at application ra-of 279 and 227 kg hauL, respectively. Homed lark

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…Even low-tillage practices disturb soil and shift debris; this displaces other rodents and is a key attraction for the deer mouse. Although the horned lark has been linked with seed removal and sprout damage to agriculture in many locales, most reports involve cultivated, irrigated crops in other regions of the US (York et al, 2000); densities are too low here. Greater threats are likely posed by deer, jack rabbits, and raccoons, especially during droughts and at harvest.…”
Section: Discussionmentioning
confidence: 96%
“…Even low-tillage practices disturb soil and shift debris; this displaces other rodents and is a key attraction for the deer mouse. Although the horned lark has been linked with seed removal and sprout damage to agriculture in many locales, most reports involve cultivated, irrigated crops in other regions of the US (York et al, 2000); densities are too low here. Greater threats are likely posed by deer, jack rabbits, and raccoons, especially during droughts and at harvest.…”
Section: Discussionmentioning
confidence: 96%
“…Enclosure trials of an AQ‐based formulation (50% AQ) sprayed on lettuce ( Lactuca sativa L.) seedlings at 2.79 kg ha −1 did not prevent damage from horned larks (i.e. 60% damage was observed) . An AQ‐based formulation (50% AQ) sprayed on lettuce seedlings at 10 L ha −1 effectively repelled horned larks within experimental enclosures (i.e.…”
Section: Avian Foliar Treatmentsmentioning
confidence: 99%
“…60% damage was observed). 61 An AQ-based formulation (50% AQ) sprayed on lettuce seedlings at 10 L ha −1 effectively repelled horned larks within experimental enclosures (i.e. 8.5% damage within treated and 68% damage within untreated enclosures).…”
Section: Lettucementioning
confidence: 99%
“…Horned lark damage to lettuce crops has motivated the use of several bird damage management techniques, including chemical repellents. Although methiocarb effectively reduced horned lark damage to lettuce seedlings in aviary tests (Cummings et al, 1998) and a field enclosure study (York et al, 2000), methiocarb is no longer registered in the U.S. as a bird repellent. Werner et al (2015) observed 38-100% feeding repellency among horned larks offered wheat seeds treated with 168-3010 ppm anthraquinone.…”
Section: Introductionmentioning
confidence: 99%